On Being Simultaneously Arab and “Modern”: Saloua Raouda Choucair’s Design Between Science and Sufism - Taan, Yasmine Nachabe (2025)
This article discusses Saloua Raouda Choucair’s commitment to design through her combined interest in science and Sufism. Her artistic and design accomplishments portray her as a resolute and determined woman who actively pursued education, independence, and progress throughout her career. By looking into Saloua’s engagement with science, technology, and mysticism, this study seeks to unravel the nuanced intersections between tradition and modernity, craftsmanship, and technology in the realm of design production. The aim is to illuminate how her utilization of scientific knowledge and Sufism shaped her design thinking, challenging prevailing norms and contributing to a broader understanding of the dynamic relationship between gender, education, and design practice in Lebanon. This research aims to interrogate the intricacies of design production by challenging the conventional dichotomy that juxtaposes tradition against modernity and craftsmanship against technology.